STRATEGI GURU DALAM MENANAMKAN SIKAP TOLERANSI SISWA SEKOLAH DASAR - Sarafina; Dafit, Febrina (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The purpose of this study is to get an impartial and complete image of: a) What is the tolerance attitude of class IV students at SDN 21 Pekanbaru; b) What is the teacher's strategy to foster tolerance in class IV students at SDN 21 Pekanbaru. This researcher implemented qualitative research using a descriptive approach. Although this type of research is descriptive and aims for researchers to easily describe teachers' strategies for instilling students' attitudes of tolerance. In this research, interviews, observation and documentation are data collection techniques. The research instruments used were questionnaire sheets, interview guide sheets and documentation. The results of the research show that: The attitude of tolerance that students have is an attitude of mutual respect and respect, such as apologizing if they make a mistake, respecting friends' opinions, not making fun of friends of different religions and being harmonious in learning activities, while the teacher's strategy is to build tolerance in class IV elementary school students. 21 Pekanbaru namely 1) by providing an example or role model to always respect every human being 2) by heterogeneous group learning with the aim of being able to work together and exchange ideas in studying material regardless of differences 3) the last strategy carried out is through habituation activities such as respect other people's opinions, do not interrupt the conversation and raise your hand before asking